2015
DOI: 10.1002/bdra.23398
|View full text |Cite
|
Sign up to set email alerts
|

Tea consumption is not associated with reduced plasma folate concentration among chinese pregnant women

Abstract: Low level of tea drinking is not associated with decreased plasma folate concentration in the Chinese populations with high and low prevalence of NTDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We used multiple linear regression to evaluate the partial correlation coefficients with 95 % CI after adjusting for confounding factors. These factors include mentioned in previous studies (age, education, delivery status, FA supplement, smoking, BMI and concentration of dietary folate adjusted by energy) (10,11,13) , imbalanced between tea consumption and no tea consumption group (ethnicity, delivery status and drinking), and other factor we are interested in may affect plasma folate levels (oral contraceptives). Then, we conducted a stratified analysis of the subjects according to ethnic groups and tea types, and we performed the same multiple linear regression analysis in each group, after adjusting for confounding factors mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used multiple linear regression to evaluate the partial correlation coefficients with 95 % CI after adjusting for confounding factors. These factors include mentioned in previous studies (age, education, delivery status, FA supplement, smoking, BMI and concentration of dietary folate adjusted by energy) (10,11,13) , imbalanced between tea consumption and no tea consumption group (ethnicity, delivery status and drinking), and other factor we are interested in may affect plasma folate levels (oral contraceptives). Then, we conducted a stratified analysis of the subjects according to ethnic groups and tea types, and we performed the same multiple linear regression analysis in each group, after adjusting for confounding factors mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…An open-label randomised crossover study revealed that consumption of green or black tea was associated with a low serum folate level for healthy volunteers (9) . A cross-sectional survey showed no association between tea drinking and plasma folate concentrations in pregnant Chinese women with high and low prevalence of NTD (10) . However, most studies did not take into account the effects of dietary folate intake, despite its being the most important factor for folate levels in the body other than FA supplement.…”
mentioning
confidence: 96%
“… 23 Notably, studies of the association between maternal tea intake during pregnancy and serum folate levels have been conducted in Japan ( n = 254) 24 and China ( n = 1,724). 25 In the former study, serum folate levels were lower among subjects who consumed large amounts of green and oolong teas, and the authors suggested that catechins might affect folate absorption. The latter study, however, failed to find an association between tea (green, oolong, black, and jasmine) intake and folate levels.…”
Section: Introductionmentioning
confidence: 94%
“…The latter study, however, failed to find an association between tea (green, oolong, black, and jasmine) intake and folate levels. 25 Despite the existence of these few studies, research concerning the associations of serum folate with caffeinated beverage intake (including green and oolong teas) and catechin levels remains limited. Therefore, the present study aimed to determine these associations in a Japanese population of pregnant women.…”
Section: Introductionmentioning
confidence: 99%